Decision Support System for Extracurricular Determination to Increase Student Involvement in Activities Outside the Classroom Using the AHP Method - Rizky Ramadhan; Yani Maulita; Br Sitepu, Kristina Annatasia (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
SMK Dharma Pancasila Medan is a private school located at Jl. Dr. T. Mansyur No.71 C Medan, Kel. PB Selayang. Currently, the selection of extracurricular activities at the school relies on a conventional manual system, lacking a formal system to identify the best extracurricular activities among the available options. This study aims to develop a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) method to evaluate and prioritize extracurricular activities based on four main criteria: achievement, short-distance running, height, and discipline. The system is designed to provide objective and measurable recommendations, facilitating students in choosing the most suitable extracurricular activities to enhance their success in out-of-class activities. The research findings demonstrate that the DSS developed with the AHP method is effective in providing accurate recommendations and increasing student engagement in extracurricular activities. The analysis and assessment process using AHP results in more targeted decisions aligned with the goal of enhancing student involvement. Overall, the system not only aids students in optimal extracurricular selection but also contributes to the development of better extracurricular activity strategies at SMK Dharma Pancasila Medan. This research enriches educational theory and practice by offering practical solutions to the challenges in extracurricular selection and enhances the overall educational experience for students.